Cost‐effectiveness of osimertinib versus placebo in resected EGFR‐mutated non‐small cell lung cancer in China. (11th June 2022) - Zhou, Xiwen; Du, Jianting; Xu, Guobing; Chen, Chun; Zheng, Bin; Chen, Jiahe
Abstract: Purpose: We aim to assess whether osimertinib postoperative adjuvant therapy, compared with placebo, is cost‐effective in China. Methods: We set up the Markov model that contains three health states over a 20‐year period. Data were collected from the ADAURA trial that included transition probabilities and safety data. Through the analysis of literature and local charges, we explore both the cost and utility values. Sensitivity analyses were employed using TreeAge Pro software to access model stability. Findings: Patients in the osimertinib group had 1.46 more Quality‐adjusted Life Years (8.45 QALYs vs 6.99 QALYs) than the placebo group at an incremental cost of 14098.51(39962.99 vs 25864.48). Compared with the placebo group, the treatment strategy with osimertinib postoperative adjuvant therapy had an incremental cost‐effectiveness ratio of 9661.97/QALY. The probability of the osimertinib‐assisted therapy strategy being cost‐effective will reach 100% if the threshold of willingness to pay is above 15, 000/QALY. Implications: From the perspective of the Chinese Healthcare System, the treatment strategy with osimertinib postoperative adjuvant therapy is more cost‐effective than the placebo strategy. Abstract : The study founds that the treatment strategy with osimertinib postoperative adjuvant therapy is more cost‐effective than the placebo strategy through setting up a Markov model. The probability of osimertinib‐assisted therapy strategy being cost‐effective will reach 100% if the threshold of willingness to pay is above 15000/QALY in China.